2012
DOI: 10.1152/ajprenal.00445.2011
|View full text |Cite
|
Sign up to set email alerts
|

The hormone melatonin stimulates renoprotective effects of “early outgrowth” endothelial progenitor cells in acute ischemic kidney injury

Abstract: Endothelial progenitor cells (EPCs) protect the kidney from acute ischemic injury. The aim of this study was to analyze whether pretreatment of murine "early outgrowth" EPCs (eEPCs) with the hormone melatonin increases the cells' renoprotective effects in the setting of murine acute ischemic renal failure. Male (8-12 wk old) C57Bl/6N mice were subjected to unilateral ischemia-reperfusion injury postuninephrectomy (40 min). Postischemic animals were injected with either 0.5×10(6) untreated syngeneic murine eEPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 38 publications
(54 reference statements)
6
60
3
Order By: Relevance
“…A recent study demonstrated that melatonin pretreatment of murine "early outgrowth" endothelial progenitor cells (eEPCs) enhanced the protective actions of these cells in mice with acute ischemic kidney damage (32), and that these effects were reversed when cells were instead cotreated with a melatonin receptor antagonist and melatonin. Furthermore, the authors observed in vitro that these eEPCs had a higher migratory ability when pretreated with melatonin (32). Also, they showed that melatonin could protect against apoptosis/necrosis induced by transforming growth factor-␤.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that melatonin pretreatment of murine "early outgrowth" endothelial progenitor cells (eEPCs) enhanced the protective actions of these cells in mice with acute ischemic kidney damage (32), and that these effects were reversed when cells were instead cotreated with a melatonin receptor antagonist and melatonin. Furthermore, the authors observed in vitro that these eEPCs had a higher migratory ability when pretreated with melatonin (32). Also, they showed that melatonin could protect against apoptosis/necrosis induced by transforming growth factor-␤.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they showed that melatonin could protect against apoptosis/necrosis induced by transforming growth factor-␤. These authors referred to melatonin as a new agonist of EPCs in acute ischemic kidney injury (32).…”
Section: Discussionmentioning
confidence: 99%
“…Both subpopulations, PACs and ECFCs have sucessfully been administered in experimental AKI [44-48]. In addition, several strategies have been established in order to augment AKI-protective effects of particularly PACs [46, 47, 49-51]. In almost all of the mentioned studies, kidney excretory function was evaluated by serum creatinine levels and additionally by certain morphological parameters such as acute tubular damage shortly (48 hours) after ischemia.…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…Thus, further studies were intended to augment the AKI-protective capacity of PACs and several pharmacological agonists of the cells were identified. Among those were melatonin [47], 8-O-cAMP [51], Bone Morphogenetic Protein-5 (BMP-5) [46], and Angiopoietin-1 [50] and -2 [49]. A more recent study showed that PACs administration post-AKI did not only prevent the kidney from acute loss of excretory function but also stabilizeed certain structural outcome parameters such as interstitial fibrosis and loss of peritubular capillaries [52].…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…In this manner, they participate in the repair of damaged tissues, thereby improving blood flow and attenuating the progression of atherosclerosis (1). Since both animal models and human studies have shown that EPCs can contribute to neovascularization and re-endothelialization, EPCs have been examined as potential treatments for various types of ischemic disease, including stroke (2), ischemic myocardium (3,4), kidney injury (5), and ischemic vascular disease (6). Moreover, it has been reported that a low EPC level is an independent risk factor for future cardiovascular events such as unstable angina and myocardial infarction (MI) (7,8).…”
Section: Introductionmentioning
confidence: 99%